Alisis Efektivitas Penrimaan Pajak Daerah Dan Retribusi Daerah Provinsi Nusa Tenggara Timur - Mite Nage, Gregorius Gery; Hanifa, Nurul (Jurnal Ekonomika : INDEPENDEN, 2023)
This study aims to determine the effectiveness of regional tax revenues and regional fees and their contribution to regional income in East Nusa Tenggara Province in 2017-2021. This study uses a quantitative research method with a descriptive approach. The data analysis technique used in this study is the effectiveness ratio analysis. The results showed that the effectiveness of regional taxes in East Nusa Tenggara Province was included in the effective category with an effectiveness of 92.07%, while the effectiveness of regional levies in East Nusa Tenggara Province was included in the quite effective category with an effectiveness of 87.05%.